FOXG1 Dose in Brain Development - Hettige, Nuwan C.; Ernst, Carl (Frontiers in Pediatrics, 2019)
Brain development is a highly regulated process that involves the precise spatio-temporal activation of cell signalling cues. Transcription factors play an integral role in this process by relaying information from external signalling cues to the genome. The transcription factor Forkhead box G1 (FOXG1) is expressed in the developing nervous system with a critical role in forebrain development. Altered dosage of FOXG1 due to deletions, duplications, or functional gain- or loss-of-function mutations, leads to a complex array of cellular effects with important consequences for human disease including neurodevelopmental disorders. Here, we review studies in multiple species and cell models where FOXG1 dose is altered. We argue against a linear, symmetrical relationship between FOXG1 dosage states, although FOXG1 levels at the right time and place need to be carefully regulated. Neurodevelopmental disease states caused by mutations in FOXG1 may therefore be regulated through different mechanisms.